CREDIT AND CREDIT SYSTEM - Allayorova Nigora Shavxiddin qizi; Dildoraxon Eshmurodova Sanjarbek qizi; Mehrbonu Eshmurodova Bobomurod qizi (Galaxy International Interdisciplinary Research Journal, 2021)
It is known that the basis of society is production. Credit plays an important role in ensuring the continuity of production.